Influências neoliberais nas políticas educacionais no Haiti: análise do Plano Operacional 2010/2015 e do Programa de Educação Universal Gratuita e Obrigatória (Psugo) - Wanchel, Pierre (2024)
This work is not part of the state's fishing, policy, and educational management. Our main object is to analyze the neoliberal influences on the configuration of the Operative Plan 2010/2015 as the origin of the free and available universal education program (PSUGO), in Haiti. These specific objects are: 1. - Present a historical panorama of the main moments of the Haitian educational system from the colonial era or period pós-ditatorial of Duvaliers. 2.- Exploring and understanding Haiti's educational policies and supporting their impact on our access to education. 3- Analyze the neoliberal influences on the configuration of the Operational Plan 2010/2015 as the origin of the free and available universal education program. Our sketch is the type of documentary analysis. A continuing theoretical argument accompanies the work of authors who deal with education, educational policies, neoliberalism, educational Desigual’s such as: Jean Luiner St Fort; (2016) François Enoque (2010 ; Menol Jeune (2014), Antoine; Daphnay (2016), Pierre (2021), Arroyo (2010), Souza (2009), Agnant (2010), Antônio ; Jean Baptiste (2019), Ball, Maguire e Braun (2016), Saviani; Demeval (2017), (L.-A. Joint, 2006, 2008), Christian Laval (2019); Dadot Pierre, Christian Laval (2016); Gentili, Pablo (1996); Anderson Perry (1995); Diaz, David Del Pino (2021), Hugo, Goeury (2020); Handards Jefferson (2008); Tardieu, 2005; 2015). These documents will be used to understand the political reforms linked to education in Haiti since 1986, considering the constitution, laws, conventions, decrees, etc. from 1987, as legal basis. In fact, the operational plan 210/2015 that gave rise to the free and compulsory universal education program was influenced by the ideas of the government's neoliberal policy; which places emphasis on the number of children who must be sent to school without thinking about a quality education; which also confirms an increase in school enrollment numbers during the years of this government compared to previous years. The Psugo program was a source of propaganda for Martelly's government. The money that was intended to finance education (Fne) for everyone was used for other purposes. Despite the presence of certain international organizations, whether to finance certain schools or to finance certain educational policy reforms, Haitian education continues to become a commodity for those who can afford it, increasingly moving away from the public sector of the poorest families.